Passively Q-switched S-band thulium fluoride fiberlaser with multi-walled carbon nanotube - Ahmad, Harith; Reduan, Siti Aisyah (Chinese Laser Press, 2018)
A stable, passively Q-switched thulium fluoride fiber laser (TFFL) using a multi-walled carbon nanotube (MWCNT)-based saturable absorber (SA) for operation in the S-band region is proposed and demonstrated. The proposed TFFL has a central lasing wavelength of 1486.4 nm and an input power range of 87.1-126.6 mW. The output pulses have a repetition rate and pulse width range of 30.1-40.0 kHz and 9.0-3.2 μs, respectively, with a maximum pulse energy of 28.9 nJ. This is the first time, to the author's knowledge, of the successful demonstration of a passively Q-switched S-band TFFL using an MWCNT-based SA.